2016
DOI: 10.1002/chem.201603608
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐induced Carboiodination: A Simple Way to Synthesize Functionalized Dihydrobenzofurans and Indolines

Abstract: Herein, we report a simple, redox-neutral and pH-neutral photo-induced carboiodination reaction under very mild conditions. This protocol employs readily available and cheap aryl bromides and sodium iodide as the starting materials to synthesize valuable functionalized dihydrobenzofurans and indolines in good to excellent yields with broad functional-group compatibility. As examples to demonstrate the utility of this protocol, gram-scale reactions and further transformations of the products were accomplished t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Very recently, Li and co-workers introduced an elegant metalfree carboiodination protocol for the syntheses of highly decorated indolines and 2,3-dihydrobenzofurans under UV radiation. 14 On the other hand, the use of visible-light as a source of energy for promoting chemical transformation has emerged as an interesting topic in organic synthesis. 15 In this sense, different research groups have demonstrated the syntheses of nitrogen-and oxygen-containing heterocyclic scaffolds using Cu(I), 16 Ir(III) 17 and Ru(II) 18 based complexes under visible-light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Li and co-workers introduced an elegant metalfree carboiodination protocol for the syntheses of highly decorated indolines and 2,3-dihydrobenzofurans under UV radiation. 14 On the other hand, the use of visible-light as a source of energy for promoting chemical transformation has emerged as an interesting topic in organic synthesis. 15 In this sense, different research groups have demonstrated the syntheses of nitrogen-and oxygen-containing heterocyclic scaffolds using Cu(I), 16 Ir(III) 17 and Ru(II) 18 based complexes under visible-light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that triplet carbonyls can abstract hydrogen atoms, especially those adjacent to heteroatoms (such as the O atom in ethers and alcohols), to produce the hydroxyalkyl radical. 44,45 Inspired by this and following our continued interest in photochemistry as a greener alternative to traditional transition-metal-catalyzed chemistry, [46][47][48][49][50][51][52][53][54] we anticipated that simply adding ketones into the reaction system would increase the generation rate of hydroxymethyl radical 15 (,CH 2 OH) because, under light irradiation, triplet ketone would be able to abstract the a-H of MeOH efficiently, 45 eventually leading to the efficient formation of direct-methylation product (16). Different from Jin and MacMillan's system 34 involving iridium photo-redox catalyst and odorous thiol organocatalyst, both of which are either expensive or not friendly to handle, we expected this system to avoid external catalysts and be driven solely by the solvent's intrinsic properties (Scheme 2B).…”
Section: Methodsmentioning
confidence: 97%
“…20,56 It was found that with this protocol, 2-methylquinoline could be tri-deuteromethylated with 76% yield (45), although other positions were also partially deuterated. Delightfully, purine-type substrate, as a key structural motif in many top-selling drugs, can also be methylated under the standard conditions (46). In addition, as important biological molecules, nicotinic acid derivatives can also be methylated with this protocol (47 and 48).…”
Section: Scope Of the Investigationmentioning
confidence: 99%
“…Photoinduced cyclization of 1-(allyloxy)-2-bromobenzenes by a simple, redox-neutral and pH-neutral photoinduced carboiodination reaction under very mild conditions was used by Li and co-workers in 2016 for the synthesis of functionalized 3-(iodomethyl)-DHBs (Scheme 46). 119 This protocol employed readily available and cheap aryl bromides and sodium iodide as the starting materials. This method gave valuable functionalized DHBs in good to excellent yields and it was also optimized on a gram-scale.…”
Section: Syn Thesismentioning
confidence: 99%